Kekerabatan Bahasa Melayu Jambi dan Melayu Palembang - Sholeha, Monita; Hendrokumoro (UPA Bahasa Universitas Tidar And HISKI Kedu, 2022)
This research describes the genetic relationship between Jambi Malay and Palembang Malay language. Related research is still rarely done, so this research needs to be carried out. This study describes the percentage of genetic relationship (lexicostatistics), separation time (glotochronology), correspondence devices, and phonological changes that occur in both languages. The main theory used in this research is Keraf (1996). The data were analyzed using interview method with note and record techniques. Quantitative evidence was obtained by using lexicostatistical and glotochronological analysis techniques. The qualitative evidence is obtained by looking for phonemic correspondence and phonological changes that occur in the languages that being compared. The results of this research showed that lexicostatistically, Jambi Malay and Palembang Malay were related by 76%. Glotochronologically, the Jambi Malay and Palembang Malay language separated in the years 1.276-1.462 (2022).). Qualitatively, six sets of phonemic correspondence and three types of phonological changes were found.